Dicer structure and function: conserved and evolving features - Zapletal, David; Kubicek, Karel; Svoboda, Petr; Stefl, Richard (EMBO reports, 2023)
RNase III Dicer produces small RNAs guiding sequence-specific regulations, with important biological roles in eukaryotes. Major Dicer-dependent mechanisms are RNA interference (RNAi) and microRNA (miRNA) pathways, which employ distinct types of small RNAs. Small interfering RNAs (siRNAs) for RNAi are produced by Dicer from long double-stranded RNA (dsRNA) as a pool of different small RNAs. In contrast, miRNAs have specific sequences because they are precisely cleaved out from small hairpin precursors. Some Dicer homologs efficiently generate both, siRNAs and miRNAs, while others are adapted for biogenesis of one small RNA type. Here, we review the wealth of recent structural analyses of animal and plant Dicers, which have revealed how different domains and their adaptations contribute to substrate recognition and cleavage in different organisms and pathways. These data imply that siRNA generation was Dicer's ancestral role and that miRNA biogenesis relies on derived features. While the key element of functional divergence is a RIG-I-like helicase domain, Dicer-mediated small RNA biogenesis also documents the impressive functional versatility of the dsRNA-binding domain.
Keywords: mikro RNA; miRNA; Dicer; malá interferující RNA; MicroRNAs; helicase; ribonukleasa III; dvouvláknová RNA; dsRBD; siRNA; zvířata; RNA Interference; RNA, Double-Stranded; Ribonuclease III; RNA, Small Interfering; RNA interference; Animals